THE ROLE OF COMPLIANCE AND GRATITUDE IN IMPROVING THE PSYCHOLOGICAL WELL-BEING OF EARLY CHILDHOOD EDUCATION TEACHERS: A LITERATURE REVIEW - Ningsih, Yuniati; Farid, Muhammad; Arifiana, Isrida Yul (International Journal Multidisciplinary (IJMI), 2026)
Objective: This study aims to comprehensively review the role of obedience and gratitude in improving the psychological well-being of non-civil servant early childhood education (PAUD) teachers, particularly in Islamic boarding schools (pesantren). Early childhood education (PAUD) teachers face significant challenges related to financial well-being, employment status, and high workloads, which have the potential to cause stress and reduce psychological well-being. Method: Through a literature review, this study found that obedience based on self-awareness, religious values, and moral responsibility can provide a sense of security, order, and satisfaction in carrying out tasks. Results: Meanwhile, gratitude has been shown to play a significant role in fostering positive emotions, reducing stress, strengthening social relationships, and helping teachers interpret limitations as a form of devotion. In the context of Islamic boarding school culture, the value of obedience reflected in the philosophy of "Bhuppa' Bhâbbhu' Ghuru Rato" and gratitude rooted in religious teachings strengthen teachers' resilience to remain dedicated. Thus, it can be concluded that obedience and gratitude are important psychological factors that complement each other in maintaining the psychological well-being of PAUD teachers. Novelty: These findings have practical implications for schools, Islamic boarding school foundations, and the government in formulating development strategies and policies that support the welfare of non-civil servant PAUD teachers more comprehensively.